Functional Nucleic Acid-Based Live-Cell Fluorescence Imaging - Zhang, Yutong; Du, Yulin; Zhuo, Yuting; Qiu, Liping (Frontiers in Chemistry, 2020)
Cell is the fundamentally structural and functional unit of life. It serves as a key research object in various biological processes, such as growth, ontogeny, metabolism and stress. Studying the spatiotemporal distribution and functional activity of specific biological molecules in living cells is crucial for exploring the mechanism governing life. It also aids in elucidation of the pathogenesis, clinical prevention and disease theranostics. In recent years, the fluorescence imaging technique has exploited to its great potential for live-cell imaging. However, the development of molecular probes has lagged far behind. Functional nucleic acids (FNAs), such as aptamer and DNAzyme, can recognize target molecules with high affinity and specificity, hence severing as prominent tools for cellular imaging. The current mini review focuses on the applications of FNAs in live-cell fluorescence imaging.